2015
DOI: 10.1111/sjop.12212
|View full text |Cite
|
Sign up to set email alerts
|

The transmission of attachment across generations: The state of art and new theoretical perspectives

Abstract: The paper reviews the body of research testing the intergenerational transmission of attachment and the theoretical shift from the linear or mediation model (van IJzendoorn, 1995), according to which parental sensitivity is the main factor responsible for the correspondence between maternal and infant's attachment, to the ecological model of the transmission of attachment (van IJzendoorn & Bakermans-Kranenburg, 1997). This latter model has prompted researchers, over time, to identify potential mediators, other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 98 publications
2
10
0
Order By: Relevance
“…In three studies, Unresolved parental AAI status, as identified before the birth of the first child and thus indicative of a representational state present before any possible influence of this or another child, was found predictive of infant Disorganized attachment (mothers and infants: Fonagy, Steele, & Steele, 1991 ; Ward & Carlson, 1995 ; fathers and infants: Steele, Steele, & Fonagy, 1996 ). Similar results replicating the link between Unresolved and Disorganized attachment status across multiple studies have been found in a recent meta-analysis focusing largely on non-English-speaking countries (Settee, Coppola, & Cassibba, 2015 ). Finally, in the most recent and most comprehensive meta-analysis conducted to date ( N = 4819; Verhage et al, 2016 ), Unresolved versus non-Unresolved classifications continued to yield significant effect sizes predicting infant Disorganized attachment status for both published and unpublished data (though weaker in the latter case).…”
supporting
confidence: 86%
“…In three studies, Unresolved parental AAI status, as identified before the birth of the first child and thus indicative of a representational state present before any possible influence of this or another child, was found predictive of infant Disorganized attachment (mothers and infants: Fonagy, Steele, & Steele, 1991 ; Ward & Carlson, 1995 ; fathers and infants: Steele, Steele, & Fonagy, 1996 ). Similar results replicating the link between Unresolved and Disorganized attachment status across multiple studies have been found in a recent meta-analysis focusing largely on non-English-speaking countries (Settee, Coppola, & Cassibba, 2015 ). Finally, in the most recent and most comprehensive meta-analysis conducted to date ( N = 4819; Verhage et al, 2016 ), Unresolved versus non-Unresolved classifications continued to yield significant effect sizes predicting infant Disorganized attachment status for both published and unpublished data (though weaker in the latter case).…”
supporting
confidence: 86%
“…A central issue in attachment theory is the intergenerational transmission of attachment styles. Both attachment and clinical sources support the style transmission from a generation to the next ( Bowlby, 1969/1982 , 1973 , 1980 ; Guidano and Liotti, 1983 ; Guidano, 1987 , 1991 ; Bretherton, 1993 ; Van Ijzendoorn, 1995 ; Bernier et al, 2014 ; Sette et al, 2015 ; Verhage et al, 2016 ; Van Ijzendoorn and Bakermans-Kranenburg, 2019 ). According to this phenomenon, a child will most likely acquire the style of their main caregiver.…”
Section: Attachment Theory: Three Major Problems Concerning Personalitymentioning
confidence: 98%
“…Given that the attachment dimensions of anxiety and avoidance are stable personality aspects (Waters et al, 2000), these dimensions should be accurately assessed in interventions aiming to reduce recidivism. Also, attachment dimensions are thought to be transgenerational in nature (Sette et al, 2015) as is the tendency to perpetrate IPV (Capaldi et al, 2012). Considering that IPV-related treatment interventions are frequently brief, group-based, largely psychoeducational in their orientation and the evidence for their effectiveness is weak, research is needed to improve the response to male perpetrators of IPV (Tarzia et al, 2020).…”
Section: Future Research Directionmentioning
confidence: 99%